نحو بناء نظم للتنبؤ والإنذار المبكر بانهيار أسواق رأس المال العربية - مدانــي, أحمـــد (Recherches économiques et managériales; Vol. 21 (2017): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES, 2018)
تتطرق هذه الورقة البحثية إلى واحدة من الآليات المهمة لاستقرار أسواق رأس المال، تتمثل في نظم الإنذار المبكر لما لها من دور مهم في رصد مدى إمكانية تعرض هذه الأسواق لأزمات انهيارها، ومن ثم يمكن أخذ الإحتياطات وتدبير أساليب لمواجهتها في وقت كافي . وفي ظل مساعي تحرير الحسابات الرأسمالية للعديد من أسواق رأس المال العربية، تبرز الحاجة القوية إلى هذه النظم ببذل الجهود والإقتداء بالتجارب الدولية لابتكارها وتصميمها وبنائها وتطبيقها، وتذليل الصعوبات التي تقف عائقاً أمام تحقيق هذا الغرض . الكلمات المفتاحية : أسواق رأس المال العربية، الأزمات المالية، الإبتكار، نظم الإنذار المبكر . Abstract: This research paper refers to one of the important mechanisms for the stability of capital markets, this mechanism is " early warning systems " because it has an important role in detecting the extent to which these markets can be hit by crises and collapses, thus allowing the taking of necessary precautions and develop methods to confront them in sufficient time. In the context of the efforts of capital account liberalization of many Arab Capital Markets, the strong need appears to these systems Through a lot of efforts and following the international experiences for innovation, design, construction and application them, and to eliminate the difficulties that stand in the way of realization this purpose. Keywords : Arab Capital Markets, financial crises, innovation, early warning systems.